2017
DOI: 10.1055/s-0043-119883
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Autonomic Dysfunction in Offspring of Hypertensive Parents During Exercise

Abstract: Offspring of hypertensive parents present autonomic dysfunction at rest and during physiological maneuvers. However, the cardiac autonomic modulation during exercise remains unknown. This study tested whether the cardiac autonomic modulation would be reduced in offspring of hypertensive parents during exercise. Fourteen offspring of hypertensive and 14 offspring of normotensive individuals were evaluated. The groups were matched by age (24.5±1.0 vs. 26.6±1.5 years; p=0.25) and BMI (22.8±0.6 vs. 24.2±1.0 kg/m; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Twenty [8,15–20,22,27,31,33,35,37–39,41] and 34 studies [8–28,31–33,36,37,39–42] reported body mass and BMI data, respectively. Some studies were matched according to body mass or BMI to a control group FHH − [12,40].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty [8,15–20,22,27,31,33,35,37–39,41] and 34 studies [8–28,31–33,36,37,39–42] reported body mass and BMI data, respectively. Some studies were matched according to body mass or BMI to a control group FHH − [12,40].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows a flowchart of selected studies. Among the 38 studies included in the quantitative analysis, with 2025 participants with ~25 years old, 21 included only men [11,12,[15][16][17][20][21][22][23][24][25]27,[31][32][33][34][35][36], five included only women [18,28,37,38], and 12 both sexes [8][9][10]13,14,19,26,[39][40][41][42]. Of these studies, 37 assessed clinic BP, 18 HRV indices, and five ambulatory BP.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations